IN VITRO ANTIOXIDANT AND ANTI-AGING ACTIVITY OF KESUM LEAVES (Polygonum minusHUDS.) ETHANOL EXTRACT - Winanta, Aji; Agustin S, Salwa Dwi; Fitri, Dhiva Andarika; Gumilang, Tresna Sriwahyuni (Usadha Journal of Pharmacy, 2024)
Skin aging is a biological process in humans characterized by the skin becoming rough or scaly, dry, black spots appearing, dull, and even wrinkles. The study was conducted to determine the biological activity of kesum leaves (Polygonum minus Huds.) as an anti-aging active ingredient in vitro. The process of making the extract using the maceration method. Secondary metabolites were identified using a phytochemical screening test. Antioxidant activity was measured using the free radical scavenging test of 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)(ABTS). The inhibitory effect of skin-degrading enzymes was measured by the percentage of inhibition of the collagenase enzymes. Based on phytochemical screening, the ethanolic extract of kesum leaves contains flavonoids, saponins, and tannins. The results of the antioxidant activity of kesum leaves have an IC50value of 41.46 g/mL and are included in the category of strong antioxidants. The results of collagenase enzyme inhibition showed that at concentrations of 50, 100, and 200 g/mL, collagenase activity could inhibit collagenase activity by 83%, 82%, and 82%. Based on the results of the research that has been carried out, it was found that the ethanol extract of the tested kesum leaves has antioxidant activity and has the potential to anti-aging.